Against the Reformists: A Study of the Sundanese Tafsir Malja’ At-Thalibin by Haji Ahmad Sanusi - Mujiburrohman Mujiburrohman; Najihah Abd Wahid (Universitas Nurul Jadid, 2024)
The background of this research is that tafsir has patterns and characteristics whose development can be influenced by the text, context, and interpretation of the interpreter from time to time. Malja’ at-Thalibin, a Sundanese tafsir by Ahmad Sanusi, is interesting to study because it was born in the socio-religious context of the Priangan region. The purpose of this research is to explore Ahmad Sanusi’s response to interpreting the Qur’an as resistance to the reformist lawsuit in which this group moves on the factor of wanting a return to the Qur’an and Sunnah, which is used as a starting point in assessing the truth in religion and community culture. This research uses a descriptive qualitative method sourced from literature studies with a content analysis approach. The depth of knowledge and insight possessed by the author shows its own satisfaction in dealing with community problems through the interpretation of the Qur'an, in addition to the combination of culture, society, and language that is able to give birth to a high-value work of interpretation and influence its readers. In addition, this tafsir also illustrates the attitude of the ulama in the context of resistance to the reformists.